RanBPM associates with CD39 and modulates ecto-nucleotidase activity - Wu, Yan (Portland Press Ltd., 2006)
CD39/ecto-NTPDase 1 (nucleoside triphosphate diphosphohydrolase 1) is an ecto-nucleotidase that influences P2 receptor activation to regulate vascular and immune cell adhesion and signalling events pivotal in inflammation. Whether CD39 interacts with other membrane or cytoplasmic proteins has not been established to date. Using the yeast two-hybrid system, we note that the N-terminus of CD39 binds to RanBPM (Ran binding protein M; also known as RanBP9), a multi-adaptor scaffolding membrane protein originally characterized as a binding protein for the small GTPase Ran. We confirm formation of complexes between CD39 and RanBPM in transfected mammalian cells by co-immunoprecipitation studies. Endogenous CD39 and RanBPM are also found to be co-expressed and abundant in cell membranes of B-lymphocytes. NTPDase activity of recombinant CD39, but not of N-terminus-deleted-CD39 mutant, is substantially diminished by RanBPM co-expression in COS-7 cells. The conserved SPRY [repeats in splA and RyR (ryanodine receptor)] moiety of RanBPM is insufficient alone for complete physical and functional interactions with CD39. We conclude that CD39 associations with RanBPM have the potential to regulate NTPDase catalytic activity. This intermolecular interaction may have important implications for the regulation of extracellular nucleotide-mediated signalling.